Pneumomediastinum and pneumopericardium in an 11-year-old rugby player: a case report - Vanzo, V.; Bugin, S.; Snijders, D.; Bottecchia, L.; Storer, V.; Barbato, A. (Journal of Athletic Training, 2013)
Objective: Pneumomediastinum and pneumopericardium are rare occurrences in young athletes, but they can result in potentially life-threatening consequences. Background: While involved in a rugby match, an 11-year-old boy received a chest compression by 3 players during a tackle. He continued to play, but 2 hours later, he developed sharp retrosternal chest pain. A chest radiograph and an echocardiograph at the nearest emergency department showed pneumopericardium and pneumomediastinum. Differential Diagnosis: Sternal and rib contusions, rib fractures, heartburn, acute asthma exacerbation, pneumomediastinum, pneumopericardium, pneumothorax, traumatic tracheal rupture, myocardial infarction, and costochondritis (Tietze syndrome). Treatment: Acetaminophen for pain control. Uniqueness: To our knowledge, this is the only case in the international literature of the simultaneous occurrence of pneumomediastinum and pneumopericardium in a child as a consequence of blunt chest trauma during a rugby match. Conclusions: Pneumomediastinum and pneumopericardium may be consequences of rugby blunt chest trauma. Symptoms can appear 1 to 2 hours later, and the conditions may result in serious complications. Immediate admission to the emergency department is required.